OPTIMASI MIX DESIGN K 350 PADA BETON PRECAST - Kuncoro Kuncoro (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2019)
Currently the price of cement is getting more expensive. Competition among precast concrete producers is increasing, especially the production of box culvert. The desire of most markets is the culvert box that meets the strength / strength standard with the emphasis on production costs. Mix Design Engineering aims to reduce the cement content and maintain the strength of Concrete and lower production costs. This research was conducted by engineering or optimizing the use of content cement and rock ash substitution against Lumajang Sand K-350 concrete mix. The most efficient results were using cement as much as 325 kg, natural sand 530 kg, dust stone 230 kg, crushed stone 1-2 795 kg, crushed stone 5-10 340 kg, water 83,51 liter, additive Consol N15 4,6 liter. Efficiency obtained from the mix design is IDR 47.692, - / m3.